Degradable super absorbent resin and preparation method thereof
Through the synergistic action of modifying acylated chitosan and introducing hydrolyzed tannins and cutinase, a degradable highly absorbable resin with high biodegradability, absorption and mechanical properties is prepared, solving the environmental pollution and mechanical strength reduction of traditional resins. The problem.
Patent Information
- Application Number
- CN202411718146.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-07
AI Technical Summary
Traditional highly absorbent resins are non-degradable, resulting in environmental pollution, and the mechanical strength decreases after adding degradable materials, making it difficult to achieve true degradability and high absorption properties.
By introducing a natural crosslinking agent to modify acylated chitosan, combined with hydrolyzed tannins and cutinase, the synergistic effect of surface crosslinking solution and cutinase solution was used to prepare a high biodegradable, absorbing and mechanical properties with high biodegradable properties, absorption and mechanical properties. Degradable highly absorbent resin.
Degradable highly absorbent resin with a biodegradation rate of more than 95% has been achieved, maintaining a high level of absorption and mechanical properties, and solving the problems of environmental pollution and mechanical strength of traditional resins.
Smart Images

Figure BSA0000299840920000061
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional polymer materials, and in particular relates to a degradable high water-absorbent resin and a preparation method thereof. Background Art
[0002] Super absorbent resin is a polymer with a three-dimensional network structure that can absorb hundreds to thousands of times its own weight of water. Different application areas have different requirements for its performance. It can be used for soil water retention, slow-release fertilizers, etc. to improve the growth quality and yield of crops; it can also be used for wound dressings, drug slow release, etc., with good water absorption and biocompatibility; it is especially suitable for sanitary products such as baby diapers and adult incontinence products, which can quickly absorb a large amount of liquid and keep it dry.
[0003] Most traditional super absorbent resins are made from non-degradable acrylic materials, which bring many problems to the environment. On the one hand, it is difficult to decompose naturally after use, and long-term accumulation will cause serious pollution to the soil, water and other environments; on the other hand, the treatment of non-degradable super absorbent resins requires special methods, such as incineration and landfilling, which are not only costly, but may also cause secondary pollution. Therefore, the development of degradable super absorbent resins is of great practical significance.
[0004] At present, the degradable super absorbent resin is mainly prepared by polymerizing corn starch, sodium alginate and sodium acrylate, but the biodegradability is average, and only the added degradable materials can be degraded, and further increasing the amount of degradable materials will greatly reduce the mechanical strength of the super absorbent resin. Therefore, the above problems must be overcome to make the super absorbent resin truly degradable without reducing the absorption performance and mechanical properties of the super absorbent resin. Summary of the invention
[0005] The present invention aims to overcome the shortcomings of the above problems and provide a degradable super absorbent resin with excellent biodegradability, a 105-day biodegradation rate of more than 95%, high absorption capacity, good water retention performance, good mechanical properties and salt resistance, and a preparation method thereof.
[0006] The technical scheme for preparing the degradable super absorbent resin of the present invention is as follows:
[0007] A degradable super absorbent resin and a preparation method thereof, characterized in that the steps include: (1) preparing a 3wt% acetic acid solution and placing it in a flask, weighing chitosan and adding it to the acetic acid solution and stirring until dissolved, then adding 10-50mL of anhydrous ethanol, and then adding 4-10mL of pyridine and stirring to form a homogeneous solution, and finally adding an anhydrous ethanol solution containing maleic anhydride to the flask, reacting at room temperature for 4-6h to obtain a primary product, precipitating the primary product with 100-500ml of anhydrous ethanol, centrifuging, washing with distilled water, and drying in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) mixing deionized water and acrylic acid uniformly, adding sodium hydroxide aqueous solution at room temperature to neutralize, and controlling The neutralization degree of acrylic acid is 50-90 mol%, and tannic acid is added to the acrylic acid neutralization solution, and the mixture is stirred and mixed uniformly; (3) a crosslinking agent acylated chitosan and an initiator ammonium persulfate are added to the solution prepared in step (2) at room temperature, and the reaction is continued to obtain a crude water-absorbent resin product, and the crude water-absorbent resin product is cut into blocks, dried in an oven, crushed, and sieved to obtain water-absorbent resin particles; (4) the water-absorbent resin particles are post-treated with a surface crosslinking liquid, and the treated water-absorbent resin is placed in an oven at 160-200° C. for drying, and then the water-absorbent resin particles are post-treated with a cutinase solution, dried at room temperature, and sieved to obtain a degradable superabsorbent resin.
[0008] According to the preparation method, the deacetylation degree of chitosan is 98%, and the mass ratio of chitosan to maleic anhydride is 2-5.
[0009] In the preparation method, the tannic acid is hydrolyzed tannin, and the added amount is 10wt%-30wt% of the acrylic acid.
[0010] In the preparation method, the added amount of acylated chitosan is 0.005wt%-0.05wt% of acrylic acid.
[0011] In the preparation method, the amount of ammonium persulfate added is 0.05wt%-0.2wt% of acrylic acid.
[0012] The preparation method comprises a surface crosslinking liquid comprising a surface crosslinking agent, an alcohol compound and water, the addition amount of which is 2wt% to 5wt% of the degradable super absorbent resin, wherein the surface crosslinking agent is at least one of bisphenol A divinyl glycidyl ether, ethylene glycol diglycidyl ether and glycerol triglycidyl ether, the addition amount of which is 5wt% to 20wt% of the surface crosslinking liquid, wherein the alcohol compound is at least one of methanol, ethanol, glycerol, butanediol and propylene glycol, the addition amount of which is 1wt% to 5wt% of the surface crosslinking liquid.
[0013] In the preparation method, the added amount of cutinase is 0.01wt% to 0.1wt% of the degradable super absorbent resin.
[0014] The beneficial effects of the present invention include:
[0015] (1) The present invention not only gives the super absorbent resin better degradation performance by introducing a natural crosslinking agent to modify the acylated chitosan, but also improves the absorption performance, water retention performance and mechanical strength of the super absorbent resin. Chitosan can form a strong intermolecular force in the solution, and its molecular rigidity is strong, so it can only be dissolved in acid and acidic aqueous solution, which greatly limits its promotion and application. The invention adopts maleic anhydride to modify chitosan to obtain water-soluble acylated chitosan with unsaturated C=C, -COOH groups. Compared with the commonly used crosslinking agent N,N-methylenebisacrylamide, the acylated chitosan as a crosslinking agent has the characteristics of safety, environmental protection and good water solubility. In addition, due to the presence of carboxyl groups on the acylated chitosan molecular chain, on the one hand, the water retention capacity of the degradable super absorbent resin is improved by utilizing the binding ability of the carboxyl groups with water; on the other hand, the repulsive effect of the negative charge of the carboxyl groups is utilized to increase the spatial extension of the molecular network of the degradable super absorbent resin, and the water absorption capacity thereof is also increased, thereby achieving the dual improvement of the water absorption and water retention performance of the degradable super absorbent resin. At the same time, the presence of the six-membered ring on the acylated chitosan molecular chain can further improve the mechanical strength of the degradable super absorbent resin.
[0016] (2) The present invention imparts better degradation performance to the super absorbent resin by introducing hydrolyzed tannins and cutinase, and also improves the absorption performance and water retention performance of the super absorbent resin. Tannic acid is a natural organic compound present in many plants and is a polyphenolic compound. The chemical structure of tannic acid is complex and it is not a single compound. It can be roughly divided into two types: condensed tannins and hydrolyzed tannins. The latter has ester bonds in its molecules; cutinase is an α / β-hydrolase that can catalyze the hydrolysis of the ester bonds of insoluble polymer plant cutin. The present invention not only introduces cross-linking agents and tannic acid that can degrade themselves, but also introduces cutinase that can decompose ester bonds. Under the synergistic effect of the three, efficient and rapid biodegradation of the super absorbent resin is achieved. In addition, the hydroxyl and carboxyl groups in tannic acid have a strong ability to bind water, which helps to improve the water retention capacity of the super absorbent resin.
[0017] (3) The present invention prepares a super absorbent resin with high absorption and water retention performance, good mechanical properties and excellent biodegradability through the synergistic effect of the compounding of surface cross-linking liquid, acylated chitosan, hydrolyzed tannin and cutinase. Through the post-treatment of the surface cross-linking liquid of the present invention, a "core-shell" structure can be formed on the surface of the absorbent resin particles. The "core" with a low cross-linking degree can maintain the high water absorption rate of the resin, while the "shell" with a high cross-linking degree can increase the pressurized absorption capacity of the resin. The synergistic effect of acylated chitosan and hydrolyzed tannin makes it possible for the super absorbent resin to not only maintain its mechanical properties after adding the degradable material tannic acid, but also improve its gel strength, thereby reducing the probability of gel clogging and allowing sanitary products to remain dry and fresh. DETAILED DESCRIPTION
[0018] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other arbitrarily without conflict.
[0019] Example 1
[0020] (1) Prepare a 3 wt % acetic acid solution and place it in a flask, weigh 1 g of chitosan and add it to the acetic acid solution and stir until dissolved, then add 20 mL of anhydrous ethanol, then add 4 mL of pyridine and stir to form a homogeneous solution, finally add an anhydrous ethanol solution containing 0.5 g of maleic anhydride to the flask, react at room temperature for 5 hours to obtain a primary product, precipitate the primary product with 100 ml of anhydrous ethanol, centrifuge, wash with distilled water, and dry in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) Mix deionized water and acrylic acid uniformly, add sodium hydroxide aqueous solution at room temperature to neutralize, control the neutralization degree of acrylic acid to 80 mol%, add 10 wt % tannic acid to the acrylic acid neutralization solution, and stir to mix (3) adding 0.005 wt% of crosslinking agent acylated chitosan and 0.05 wt% of initiator ammonium persulfate to the solution prepared in step (2) at room temperature, continuing the reaction, and initially obtaining a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) firstly using a surface crosslinking liquid prepared by 5 wt% of ethylene glycol diglycidyl ether and 1 wt% of propylene glycol to post-treat the water-absorbent resin particles, placing the treated water-absorbent resin in an oven at 180°C for drying, and then using 0.01 wt% of cutinase to post-treat the water-absorbent resin particles, drying at room temperature, and sieving to obtain a degradable superabsorbent resin.
[0021] Example 2
[0022] (1) Prepare a 3 wt % acetic acid solution and place it in a flask, weigh 1 g of chitosan and add it to the acetic acid solution and stir until dissolved, then add 20 mL of anhydrous ethanol, then add 4 mL of pyridine and stir to form a homogeneous solution, finally add an anhydrous ethanol solution containing 0.5 g of maleic anhydride to the flask, react at room temperature for 5 hours to obtain a primary product, precipitate the primary product with 100 ml of anhydrous ethanol, centrifuge, wash with distilled water, and dry in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) Mix deionized water and acrylic acid uniformly, add sodium hydroxide aqueous solution at room temperature to neutralize, control the neutralization degree of acrylic acid to 80 mol%, add 30 wt % tannic acid to the acrylic acid neutralization solution, and stir to mix (3) adding 0.005 wt% of crosslinking agent acylated chitosan and 0.05 wt% of initiator ammonium persulfate to the solution prepared in step (2) at room temperature, continuing the reaction, and initially obtaining a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) firstly using a surface crosslinking liquid prepared by 5 wt% of ethylene glycol diglycidyl ether and 1 wt% of propylene glycol to post-treat the water-absorbent resin particles, placing the treated water-absorbent resin in an oven at 180° C. for drying, and then using 0.01 wt% of cutinase to post-treat the water-absorbent resin particles, drying at room temperature, and sieving to obtain a degradable superabsorbent resin.
[0023] Example 3
[0024] (1) Prepare a 3 wt % acetic acid solution and place it in a flask, weigh 1 g of chitosan and add it to the acetic acid solution and stir until dissolved, then add 20 mL of anhydrous ethanol, then add 4 mL of pyridine and stir to form a homogeneous solution, finally add an anhydrous ethanol solution containing 0.5 g of maleic anhydride to the flask, react at room temperature for 5 hours to obtain a primary product, precipitate the primary product with 100 ml of anhydrous ethanol, centrifuge, wash with distilled water, and dry in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) Mix deionized water and acrylic acid uniformly, add sodium hydroxide aqueous solution at room temperature to neutralize, control the neutralization degree of acrylic acid to 80 mol%, add 30 wt % tannic acid to the acrylic acid neutralization solution, stir and mix (3) adding 0.005 wt % of cross-linking agent acylated chitosan and 0.05 wt % of initiator ammonium persulfate to the solution prepared in step (2) at room temperature, continuing the reaction, and initially obtaining a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) firstly post-treating the water-absorbent resin particles with a surface cross-linking liquid prepared with 5 wt % of ethylene glycol diglycidyl ether and 1 wt % of propylene glycol, placing the treated water-absorbent resin in an oven at 180°C for drying, and then post-treating the water-absorbent resin particles with 0.1 wt % of cutinase, drying at room temperature, and sieving to obtain a degradable superabsorbent resin.
[0025] Example 4
[0026] (1) Prepare a 3 wt % acetic acid solution and place it in a flask, weigh 1 g of chitosan and add it to the acetic acid solution and stir until dissolved, then add 20 mL of anhydrous ethanol, then add 4 mL of pyridine and stir to form a homogeneous solution, finally add an anhydrous ethanol solution containing 0.5 g of maleic anhydride to the flask, react at room temperature for 5 hours to obtain a primary product, precipitate the primary product with 100 ml of anhydrous ethanol, centrifuge, wash with distilled water, and dry in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) Mix deionized water and acrylic acid uniformly, add sodium hydroxide aqueous solution at room temperature to neutralize, control the neutralization degree of acrylic acid to 80 mol%, add 30 wt % tannic acid to the acrylic acid neutralization solution, stir and mix (3) adding 0.04wt% of crosslinking agent acylated chitosan and 0.1wt% of initiator ammonium persulfate to the solution prepared in step (2) at room temperature, continuing the reaction to initially obtain a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) firstly post-treating the water-absorbent resin particles with a surface cross-linking liquid prepared with 10wt% ethylene glycol diglycidyl ether and 5wt% propylene glycol, placing the treated water-absorbent resin in an oven at 180°C for drying, and then post-treating the water-absorbent resin particles with 0.1wt% cutinase, drying at room temperature, and sieving to obtain a degradable superabsorbent resin.
[0027] Example 5
[0028] This example tests the absorption performance, absorption speed and biodegradability of the super absorbent resins of Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3.
[0029] Absorption performance test: The absorption capacity (physiological saline), water retention capacity, and pressure absorption capacity of the super absorbent resin were tested with reference to GB / T22875-2018 "Super absorbent resin for diapers and sanitary napkins". The test results are shown in Table 1;
[0030] Absorption rate test: add 50.0±0.5g of normal saline to a 100mL beaker, adjust the magnetic stirrer to stir at a speed of 600rpm, accurately weigh 2.00g of super absorbent resin and put it into the normal saline, and use a stopwatch to time it. When the vortex of the solution disappears and the liquid surface becomes horizontal, it is taken as the end point, and the time (s) is recorded. Each sample is tested in parallel for 3 groups of data, and the average value is taken as the test result. The test results are shown in Table 1;
[0031] Biodegradability test: The test was conducted in accordance with ISO14855-1:2012 “Determination of the ultimate aerobic biodegradability of plastic materials in a controlled composting environment: Analytical method for the release of carbon dioxide”. The test results are shown in Table 1.
[0032] Comparative Example 1
[0033] (1) a 3 wt % acetic acid solution is prepared and placed in a flask, 1 g of chitosan is weighed and added to the acetic acid solution and stirred until dissolved, then 20 mL of anhydrous ethanol is added, and then 4 mL of pyridine is added to stir to form a homogeneous solution, and finally an anhydrous ethanol solution containing 0.5 g of maleic anhydride is added to the flask, and the reaction is carried out at room temperature for 5 h to obtain a primary product, the primary product is precipitated with 100 ml of anhydrous ethanol, centrifuged, washed with distilled water, and dried in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) deionized water and acrylic acid are uniformly mixed, and sodium hydroxide aqueous solution is added at room temperature for neutralization, and the neutralization degree of acrylic acid is controlled to be 80 mol%, and 30 wt % of chitosan is added. (3) adding 0.04wt% of acylated chitosan as a crosslinking agent and 0.1wt% of ammonium persulfate as an initiator to the solution prepared in step (2) at room temperature, continuing the reaction to preliminarily obtain a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) first post-treating the water-absorbent resin particles with a surface crosslinking solution prepared by 10wt% of ethylene glycol diglycidyl ether and 5wt% of propylene glycol, and placing the treated water-absorbent resin in an oven at 180°C for drying and sieving to obtain a highly absorbent resin.
[0034] Comparative Example 2
[0035] (1) Prepare a 3 wt % acetic acid solution and place it in a flask, weigh 1 g of chitosan and add it to the acetic acid solution and stir until dissolved, then add 20 mL of anhydrous ethanol, then add 4 mL of pyridine and stir to form a homogeneous solution, finally add an anhydrous ethanol solution containing 0.5 g of maleic anhydride to the flask, react at room temperature for 5 hours to obtain a primary product, precipitate the primary product with 100 ml of anhydrous ethanol, centrifuge, wash with distilled water, and dry in a vacuum constant temperature drying oven to obtain acylated chitosan; (2) Mix deionized water and acrylic acid uniformly, add sodium hydroxide aqueous solution at room temperature to neutralize, and control the neutralization of acrylic acid The concentration is 80 mol%; (3) adding 0.04 wt% of crosslinking agent acylated chitosan and 0.1 wt% of initiator ammonium persulfate to the solution prepared in step (2) at room temperature, continuing the reaction, and initially obtaining a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles; (4) firstly post-treating the water-absorbent resin particles with a surface crosslinking liquid prepared by mixing 10 wt% of ethylene glycol diglycidyl ether and 5 wt% of propylene glycol, and placing the treated water-absorbent resin in an oven at 180°C for drying and sieving to obtain a highly absorbent resin.
[0036] Comparative Example 3
[0037] Commercially available conventional super absorbent resin.
[0038] The following are the test results of the absorption capacity, water retention capacity, pressure absorption capacity, absorption speed, biodegradation and other properties of the super absorbent resins of Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3:
[0039] Table 1 Test results of absorption performance and biodegradability of different super absorbent resins
[0040]
[0041] It can be seen from Examples 1, 2, 3, 4 and Comparative Examples 1, 2, 3 that simply adding degradable materials through the polymerization process cannot achieve good biodegradability and the overall absorption performance is reduced. However, through the synergistic effect of the components of the present invention, the prepared degradable super absorbent resin not only has an absorption performance comparable to that of commercially available super absorbent resins, but also has improved mechanical properties, especially excellent biodegradability.
[0042] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A degradable super absorbent resin and a preparation method thereof, characterized in that: The following steps are involved: (1) preparing a 3 wt % acetic acid solution and placing it in a flask, weighing chitosan and adding it to the acetic acid solution and stirring until dissolved, then adding 10-50 mL of anhydrous ethanol, and then adding 4-10 mL of pyridine and stirring to form a homogeneous solution, and finally adding an anhydrous ethanol solution containing maleic anhydride to the flask, reacting at room temperature for 4-6 hours to obtain a primary product, precipitating the primary product with 100-500 ml of anhydrous ethanol, centrifuging, washing with distilled water, and drying in a vacuum constant temperature drying oven to obtain acylated chitosan, wherein the deacetylation degree of the chitosan is 98%, and the mass ratio of chitosan to maleic anhydride is 2-5; (2) mixing deionized water and acrylic acid uniformly, adding sodium hydroxide aqueous solution at room temperature for neutralization, controlling the neutralization degree of acrylic acid to be 50-90 mol%, adding tannic acid to the neutralized acrylic acid solution, stirring and mixing uniformly, wherein the tannic acid is hydrolyzed tannin, and the addition amount is 10 wt%-30 wt% of the acrylic acid; (3) adding acylated chitosan as a crosslinking agent and ammonium persulfate as an initiator to the solution prepared in step (2) at room temperature, continuing the reaction to preliminarily obtain a crude water-absorbent resin product, cutting the crude water-absorbent resin product into blocks, drying in an oven, crushing, and sieving to obtain water-absorbent resin particles, wherein the amount of acylated chitosan added is 0.005wt%-0.05wt% of the acrylic acid, and the amount of ammonium persulfate added is 0.05wt%-0.2wt% of the acrylic acid; (4) firstly post-treating the water-absorbent resin particles with a surface cross-linking liquid, placing the treated water-absorbent resin in an oven at 160-200° C. for drying, and then post-treating the water-absorbent resin particles with a cutinase solution, drying at room temperature, and sieving to obtain a degradable superabsorbent resin.
2. The method for preparing a degradable super absorbent resin according to claim 1, wherein: The surface cross-linking liquid comprises a surface cross-linking agent, an alcohol compound and water, and the addition amount is 2wt% to 5wt% of the degradable super absorbent resin; wherein the surface cross-linking agent is at least one of bisphenol A divinyl glycidyl ether, ethylene glycol diglycidyl ether, and glycerol triglycidyl ether, and the addition amount is 5wt% to 20wt% of the surface cross-linking liquid; the alcohol compound is at least one of methanol, ethanol, glycerol, butanediol, and propylene glycol, and the addition amount is 1wt% to 5wt% of the surface cross-linking liquid; and the addition amount of the cutinase is 0.01wt% to 0.1wt% of the degradable super absorbent resin.